1994
DOI: 10.1109/72.317728
|View full text |Cite
|
Sign up to set email alerts
|

Maximum likelihood training of probabilistic neural networks

Abstract: A maximum likelihood method is presented for training probabilistic neural networks (PNN's) using a Gaussian kernel, or Parzen window. The proposed training algorithm enables general nonlinear discrimination and is a generalization of Fisher's method for linear discrimination. Important features of maximum likelihood training for PNN's are: 1) it economizes the well known Parzen window estimator while preserving feedforward NN architecture, 2) it utilizes class pooling to generalize classes represented by smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(74 citation statements)
references
References 17 publications
1
72
0
1
Order By: Relevance
“…For examples, we can think of its realization by the probabilistic network of Streit and Luginbuhl (1994), and by one of the winner take-all networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For examples, we can think of its realization by the probabilistic network of Streit and Luginbuhl (1994), and by one of the winner take-all networks.…”
Section: Discussionmentioning
confidence: 99%
“…The mixture distribu tion is generally assumed in a classification problem, and its unknown parameters can be estimated using a maximum likelihood method (Streit and Luginbuhl, 1994). Of course, while the estimation in a clustering problem may be carried out in much the same way as that in a classification problem, the absence of a priori class memberships is the major difference between these two problem, and it makes the clustering problem much more difficult ; that is, the estimation will be possibly disturbed by the problem of local minima.…”
Section: Introductionmentioning
confidence: 99%
“…It is achieved by estimating probability density functions as a mixture of Gaussian densities with varying covariance matrices. In the reference Streit and Luginbuhl (1994), a maximum likelihood algorithm for training the network is presented as the generalization of Fisher method for nonlinear discrimination. It is shown that the proposed PNN requires significantly fewer nodes and interconnection weights than the original model.…”
Section: Related Workmentioning
confidence: 99%
“…Kohonen Class-Modelling (KCM) (Marini et al, 2005), and Probabilistic Neural Networks (PNN) (Streit & Luginbuhl, 1994 (Vapnik, 1998;Abe, 2005;Burges, 1998). The purpose of SVM is separate the classes in a vectorial space independently on the probabilistic distribution of pattern vectors in the data set (Berrueta et al, 2007).…”
Section: Development Of the Decision Rulementioning
confidence: 99%